Effects of impactor shape on the deformation and energy absorption of closed cell aluminium foams under low velocity impact. (June 2020) - Islam, M.A.; Kader, M.A.; Hazell, P.J.; Escobedo, J.P.; Brown, A.D.; Saadatfar, M.
Abstract: The low-velocity impact response of closed-cell aluminium foams using various shaped indenters has been investigated. Impact tests were conducted using an instrumented drop-tower with flat, hemispherical, conical and truncated-conical indenter at impact energies ranging from 46.8 J to 105 J. The effects of variation of indenter shape and impact velocity on mechanical properties and deformation mechanisms of foam have been explicitly investigated. The results show that the mechanical response of closed-cell aluminium foams under low-velocity projectile impact significantly depends on the indenters' nose shape and initial impact energy. The deformation mechanisms of foam for different shaped indenters have been elucidated using reconstructed X-ray micro-computed tomography (XCT) images of the indented specimens. A good correlation between the indenter shape and deformation mechanisms has been observed. The structure-property relations of foams during dynamic indentation have also been explored by analysing the XCT images of the indented specimens. The parameters that influence the energy absorption capacity of the material are also presented. Graphical abstract: Unlabelled Image Highlights: Dynamic indentation response of closed-cell aluminium foam depends on indenter's nose shape. Specific energy absorption increases with the increase of impact velocity. Nose shape of impactor influences the deformation behaviour and energy absorption in closed-cell foams. Deformation in dynamic indentation initiates just underneath the indenter and propagates with the indenter's movement.